Time mirroring based CSMA/CA for improving performance of UAV-relay network system - Baek, Hoki; Lim, Jaesung (IEEE Systems Journal, 2019)
Owing to easy deployment to extend network coverage, unmanned aerial vehicle (UAV) relay network systems have been widely studied. Most UAVs are equipped with wireless local area network (WLAN) and use carrier sense multiple access with collision avoidance (CSMA/CA) protocol. However, the network performance of CSMA/CA is largely degraded in UAV-relay network systems (URNSs), owing to collisions caused by contention at each hop. Thus, improving network performance is important. Moreover, there are additional requirements: Designing a lightweight UAV relay and avoiding unnecessary relays. In this paper, URNS architecture and time-mirroring CSMA/CA (TM-CSMA/CA) are proposed to satisfy these requirements. First, a URNS architecture is designed to support the lightweight relay, performed without a media access control (MAC) layer, and to avoid unnecessary relays at the UAV by only using the physical layer. Second, TM-CSMA/CA guarantees that the UAV relay always wins contention by adjusting the defer time without a MAC layer. Thus, TM-CSMA/CA provides better network performance than CSMA/CA. To the best of our knowledge, there is no mathematical model for analyzing end-to-end delay of CSMA/CA. Thus, we construct mathematical models to analyze both saturation throughput and delay of two-hop delivery of CSMA/CA and TM-CSMA/CA. The numerical results show that TM-CSMA/CA provides higher saturation throughput and lower end-to-end delay than CSMA/CA.
Keywords: Carrier sense multiple access (CSMA); Carrier sense multiple access with collision avoidances; Improving performance; Media access control; Numerical results; relay; Saturation throughput; Uav relays; Carrier sense multiple access (CSMA); relay; UAV-relay network system (URNS); unmanned aerial vehicle (UAV)